Sondheim on Music: Minor Details and Major Decisions - Horowitz, Mark Eden (Rowman & Littlefield Publishers, 2010)
Stephen Sondheim is widely regarded as the most important composer and lyricist of musical theater in the second half of the 20th century. Celebrating his 80th birthday, this new edition of Sondheim on Music finds him in these guided interviews expounding in great depth and detail on his craft. As a natural teacher, thoughtful and opinionated, Sondheim discusses the art of musical composition, lyric writing, the collaborative process of musical theater, and how he thinks about his own work. Where the first edition focused particularly on six shows—Passion, Assassins, Into the Woods, Sunday in the Park with George, Sweeney Todd, and Pacific Overtures—this second edition presents a new chapter that discusses Sondheim's entire career. Several shows that were not discussed previously are explored here, including A Funny Thing Happened on the Way to the Forum, Merrily We Roll Along, Company, Follies, Anyone Can Whistle, and A Little Night Music, as well as thoughts about the recent film adaptation of Sweeney Todd. The book also features an entire chapter on Bounce: the previous incarnation of his latest musical, Road Show. In addition to Sondheim's list of "Songs I Wish I'd Written," the songlisting and discography has been greatly expanded and updated to include all works composed and recorded over the last six years.